ヒガシ ナンキョク ミズホ コウゲン フキン ノ キショウ ジョウタイ ニ ツイテ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 上田, 豊; アゲタ, ユタカ; AGETA, Yutaka (国立極地研究所, 1971)
P(論文) The weather conditions from September to January in the vicinity of the Mizuho Plateau, the area between the coast and 72°S, are discussed on the basis of the weather observations made during the traverses of JARE-10 (the 10th Japanese Antarctic Research Expedition) in 1969-70 and the previous traverses. The mean wind speed of about 8-10 m/s is obtained from the observations. It is found that the observed orientations of sastrugis and pitted patterns show seasonal variations. The wind direction is constant in inland, but diurnal variations of the wind direction were observed. When the wind direction changes counterclockwise to the north from the prevailing wind direction, it can be expected that weather is getting worse. The flow lines of the prevailing winds in the vicinity of the Mizuho Plateau are drawn from the orientations of sastrugis and other features. The pressure variation in inland about 350 km distant from Syowa Station was similar to that at Syowa Station. Sea-salt particles were detected at 71°S and 43°E during a light snow or ice prisms falling when the wind was weak with its direction changing counterclockwise from the prevailing wind direction. departmental bulletin paper